Kegiatan Pengembangan Minat dan Bakat Pada Anak-Anak dalam Kegiatan Keagamaan di Distrik Heram Kel. Waena Kota Jayapura - Bernarda Meteray; Helen Yuliance Ester Wabiser (Jurnal DIKMAS, 2021)
Developing children's interests and talents in a religious context is crucial to shaping the character and morality of the younger generation. This study aims to explore the various methods used in religious activities in Heram District, Waena Kel. Jayapura City, and to measure their impact on the development of children's interests and talents. Through qualitative and quantitative approaches, data was collected from observations, interviews, and questionnaires. Results show that religious activities not only increase children's interest in spiritual aspects, but also contribute to their social and emotional development.